Polydopamine-Coated Laponite Nanoplatforms for Photoacoustic Imaging-Guided Chemo-Phototherapy of Breast Cancer - Renna Liu; Fanli Xu; Lu Wang; Mengxue Liu; Xueyan Cao; Xiangyang Shi; Rui Guo (Nanomaterials, 2021)
Theranostic nanoplatforms combining photosensitizers and anticancer drugs have aroused wide interest due to the real-time photoacoustic (PA) imaging capability and improved therapeutic efficacy by the synergistic effect of chemotherapy and phototherapy. In this study, polydopamine (PDA) coated laponite (LAP) nanoplatforms were synthesized to efficiently load indocyanine green (ICG) and doxorubicin (DOX), and modified with polyethylene glycol-arginine-glycine-aspartic acid (PEG-RGD) for PA imaging-guided chemo-phototherapy of cancer cells overexpressing αvβ3 integrin. The formed ICG/LAP-PDA-PEG-RGD/DOX nanoplatforms showed significantly higher photothermal conversion efficiency than ICG solution and excellent PA imaging capability, and could release DOX in a pH-sensitive and NIR laser-triggered way, which is highly desirable feature in precision chemotherapy. In addition, the ICG/LAP-PDA-PEG-RGD/DOX nanoplatforms could be uptake by cancer cells overexpressing αvβ3 integrin with high specificity, and thus serve as a targeted contrast agent for in vivo PA imaging of cancer. In vivo experiments with 4T1 tumor-bearing mouse model demonstrated that ICG/LAP-PDA-PEG-RGD/DOX nanoplatforms exhibited much stronger therapeutic effect and higher survival rate than monotherapy due to the synergetic chemo-phototherapy under NIR laser irradiation. Therefore, the reported ICG/LAP-PDA-PEG-RGD/DOX represents a promising theranostic nanoplatform for high effectiveness PA imaging-guided chemo-phototherapy of cancer cells overexpressing αvβ3 integrin.